The evolving role of tropical forests for local livelihoods in Indonesia - Basuki, I.; Sheil, Douglas; Padmanaba, M.; Liswanti, N.; Mulcahy, G.; Wan, M. (2011)
The authors studied how the role and perceptions of natural forests have changed in seven villages along the Malinau River, East Kalimantan (Indonesian Borneo). Local people consider development projects, logging and mining activities, and floods as having the greatest influence on their livelihoods and use of forests. Access to and availability of valued forest products are perceived to have decreased and thus, while still of considerable importance, the overall role of forests has declined. New sources of income, farming opportunities, clinics and access to schools, as well as the village infrastructure, are the main positive changes in local livelihoods. While village life is improving, in general, villagers are concerned about the declining quality of their forests and the environment. The present study findings indicate that forest communities, often living in remote areas, support both development and conservation efforts. Giving greater control to local people in the management of tropical forests, offers both environmental and development benefits.